Comparison of high and low stunting reduction groups using IFE-EFE matrix analysis in Central Java Province, Indonesia - Samsudin, Mohamad; Hapsari, Pramesthi Widya; Kartasurya, Martha Irene; Syauqy, Ahmad; Isnawati, Muflihah; Wati, Erna Kusuma; Nurcahyani, Yusi Dwi; Fuada, Noviati; Suyatno, Suyatno; Dewantiningrum, Julian; Sunarto, Sunarto; Nuryanto, Nuryanto (Frontiers in Public Health, 2023)
Background: The results of the 2021 Indonesian Nutritional Status Study (Survei Status Gizi Indonesia, SSGI) showed a 6.8% stunting declining prevalence in Central Java from 2019 to 2021. However, the prevalence decreases in the regency level of Central Java varied from 0.1% to 20.3%. This study aimed to analyze the external and internal factors which influenced the stunting reduction prevalence in Central Java Province, Indonesia. Methods: This qualitative study was conducted over two months, from April to May 2022. In-depth interviews were used to explore the supporting factors (external, internal, and strategies) and the challenges (internal, external, and solutions) in implementing stunting reduction acceleration programs. The supporting factors and challenges were compared between the groups with high (Grobogan, Sragen, Klaten, and Pekalongan regencies or GSKP) and low (Surakarta, Magelang, Tegal, and Pati or SMTP) reduction prevalence. Data were analyzed using Internal Factor Evaluation (IFA) and External Factor Evaluation (EFE). Results: In Quadrant II, the high-reduction group (GSKP) had IFE and EFE scores of 2.61 and 2.76, respectively. In Quadrant IV, the low-reduction group (SMTP) had IFE and EFE scores of 1.86 and 1.62, respectively. The high-reduction group (GSKP) was better than the low-reduction group (SMTP) in using external opportunities and internal strengths by avoiding external threats and minimizing the weakness in the stunting reduction acceleration program in each area. The existence of superior programs and innovations were the strengths that differentiated the high and low groups. Conversely, the low stunting reduction group struggled to overcome major challenges, especially lacking leadership capacity. From the outside, lack of program sustainability at the village level and budget restraint were the threats found in both groups. Conclusion: Compared to the low stunting reduction group, the high group could maximize their strengths and use the opportunities to implement stunting reduction programs. Keywords: stunting, factor analysis, internal factor evaluation, external factor evaluation, SWOT analysis, qualitative research